Cross-border Marriages and Mobility : Female Chinese Migrants and Hong Kong Men - Binah-Pollak, Avital (Book collections on Project MUSE., 2019)
This book focuses on cross-border marriages between mainland Chinese women and Hong Kong men, a phenomenon which is of critical importance to the transformation of Hong Kong. Based on ethnographic work, Avital Binah-Pollak aims to explain the relationships between gender dynamics and inequalities at the level of the family and broader social, political, and economic relationships between mainland China and Hong Kong. She argues that these cross-border marriages are causing the expanding and blurring of borders, so that there is a much wider strip of border in which the dichotomies of the rural/urban, periphery/center, and hybrid/national identities become more complex and negotiable. While this is particularly interesting and valid in the case of the border between mainland China and Hong Kong because of the particular nature of the relationship between these two societies, it may also apply to borders between many other societies worldwide.